Antioxidant and Neuroprotective Potential of the Brown Seaweed Bifurcaria bifurcata in an in vitro Parkinson’s Disease Model - Joana Silva; Celso Alves; Rafaela Freitas; Alice Martins; Susete Pinteus; Joana Ribeiro; Helena Gaspar; Amparo Alfonso; Rui Pedrosa (Marine Drugs, 2019)
Bifurcaria bifurcata is a marine brown seaweed mainly found on the Atlantic coast. Herein, we report the antioxidant and neuroprotective activities of seven fractions (F1⁻F7) obtained by normal phase chromatography from the B. bifurcata dichloromethane extract, as well as of its two major isolated diterpenes. Total phenolic content of fractions was determined by the Folin⁻Ciocalteu method, while antioxidant activity was evaluated by the DPPH, ORAC, and FRAP assays. Neuroprotective effects were evaluated in a neurotoxic model induced by 6-hydroxydopamine (6-OHDA) in a human neuroblastoma cell line (SH-SY5Y), while the mechanisms associated to neuroprotection were investigated by the determination of mitochondrial membrane potential, H2O2 production, Caspase-3 activity, and by observation of DNA fragmentation. Fractions F4 and F5 exhibited the best neuroprotective and antioxidant activities, respectively. F4 fraction prevented changes in mitochondrial potential, and induced a reduction of H2O2 levels production and an increase in cell viability, suggesting that it may contain multi-target compounds acting on different pathways. Hence, this fraction was subjected to purification steps, affording the known diterpenes eleganolone and eleganonal. Both compounds exhibited antioxidant potential, being interesting candidates for further neuroprotective studies.